1989
DOI: 10.1159/000185291
|View full text |Cite
|
Sign up to set email alerts
|

Restrictions on Use of Creatinine Clearance for Measurement of Renal Functional Reserve

Abstract: The increase of glomerular filtration rate after a 90-gram oral protein load was determined in 9 healthy individuals by simultaneous measurements of both creatinine (Ccr) and inulin (Cin) clearances, performed before and every 30 min during 4 h after the meat meal. This protein load resulted in a short 26% increase of Cin at 90 min, and a sustained 29% increase of Ccr from 90 to 240 min after load. Individual peak values of Ccr occurred later than those of Cin (Ccr: 189 ± 19 vs. Cin: 127 ± 19 min;p = 0.023). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 8 publications
2
15
0
1
Order By: Relevance
“…However, the use of creatinine clearance has many drawbacks in assessing GFR and RFR, specially in renal disease. After a meat meal, plasma creatinine concentration increases significantly as reported by Laville et al [13] and Shomesh et al [14] who showed the inaccuracy of this method for determination of renal reserve after a meat meal and in renal disease. Since DTPA is a glomerular agent excreted solely by the glomerulus and not affected by meat meal, we have …”
Section: Discussionsupporting
confidence: 58%
“…However, the use of creatinine clearance has many drawbacks in assessing GFR and RFR, specially in renal disease. After a meat meal, plasma creatinine concentration increases significantly as reported by Laville et al [13] and Shomesh et al [14] who showed the inaccuracy of this method for determination of renal reserve after a meat meal and in renal disease. Since DTPA is a glomerular agent excreted solely by the glomerulus and not affected by meat meal, we have …”
Section: Discussionsupporting
confidence: 58%
“…However, on the experience made in our laboratory and on the analysis of available information, we would like to elicit a few certainties: (1) an oral protein load in form of a beefsteak prepared without adding sodium, oil or butter, and served without bread/crackers, is asso ciated with a constant reserve; (2) protein and Na intake should be assessed at the time of the evaluation of the reserve; (3) GFR should be measured with inulin since creatinine is inadequate [18,22,27]; (4) hemodynamic response may occur within as early as 30 min in healthy children and within 60 min in renal failure; (5) early GFR response is not dependent on insulin, renin, aldosterone, or on plasma amino acid concentration; (6) during hem odynamic response, the tubulo-glomerular feedback mechanism is normal but the quantity of fluid and so dium delivered from the proximal tubule continuously increases, perhaps due to the changes in plasma insulin; (7) the reserve in early renal disease may be normal but its relationship to protein intake remains undetermined; (8) patients with single kidneys, children with type 1 diabetes mellitus, children with renal failure and high to normal protein intake and children with reduced GFR may all show a reduced renal functional reserve.…”
Section: Discussionmentioning
confidence: 99%
“…Only in 2 of 12 studies (table 3), a renal reserve was present following a protein meal in children with renal disease. However, only 30 of 122 children were studied by inulin and the remaining by creatinine clearance which is not optimal under such experimental conditions [27], Furthermore, only in studies N and P was the protein intake established at the time of the study, whereas all studies lack information on Na intake which is a determi nant of renal reserve [13,28].…”
Section: Renal Reserve In Children With Renal Diseasementioning
confidence: 99%
“…Data shown in this study are preliminary and intend to only suggest that RST is a useful, feasible, and cost-effective analysis that should be included in routine clinical practice for living donors kidney transplantation. Second, we used sCr, instead of inulin, as marker solute to quantify the renal clearance and thus the GFR [44,45] . Although potentially overestimated, the GFR obtained with this method is noninvasive, inexpensive, repeatable, and thus clinically applicable in daily routine practice.…”
Section: Discussionmentioning
confidence: 99%